Liraglutide protects Rin‐m5f β cells by reducing procoagulant tissue factor activity and apoptosis prompted by microparticles under conditions mimicking Instant Blood‐Mediated Inflammatory Reaction3. (24th March 2014) - Gleizes, Céline; Constantinescu, Andrei; Abbas, Malak; Bouhadja, Houda; Zobairi, Fatiha; Kessler, Laurence; Toti, Florence
Summary Instant Blood‐Mediated Inflammatory Reaction (IBMIR) occurs at the vicinity of transplanted islets immediately after intraportal infusion and is characterized by cytokine secretion, tissue factor (TF) expression, and ß cell loss. Microparticles (MPs) are cellular effectors shed from the plasma membrane of apoptotic cells. Modulation of the properties of ß cell‐derived MPs by liraglutide was assessed in a cellular model designed to mimic IBMIR oxidative and inflammatory conditions. Rin‐m5f rat β cells were stimulated by H2O2 or a combination of IL‐1β and TNF‐α. Cell‐derived MPs were applied to naive Rin‐m5f for 24 h. Apoptosis, MP release, TF activity, P‐IκB expression, and MP‐mediated apoptosis were measured in target cells. Direct protection by liraglutide was shown by a significant decrease in the oxidative stress‐induced apoptosis (18.7% vs. 7.6%, P < 0.0001 at 1 μm liraglutide) and cellular TF activity (−40% at 100 nm liraglutide). Indirect cytoprotection led to 20% reduction in MP generation, thereby lowering MP‐mediated apoptosis (6.3% vs. 3.7%, P = 0.022) and NF‐κB activation (−50%) in target cells. New cytoprotective effects of liraglutide were evidenced, limiting the expression of TF activity by ß cells and the generation of noxious MPs. Altogether, these data suggest that liraglutide could target pro‐apoptotic and pro‐inflammatory MPs in transplanted islets.